Oral Histoplasmosis with Previously Treated Pulmonary Tuberculosis: A Case Report (Medicine Today, 2014)
Oral Histoplasmosis is a deep fungal infection may present as oral ulceration and can be confused with oral mucosal malignancies, tuberculosis and other fungal diseases. It mostly affects individual having immunodeficiencies like tuberculosis and AIDS, but may also affect immunocompetent individuals. Here we presented a case of oral histoplasmosis with previously treated pulmonary tuberculosisand was treated by oral itraconazole. Complete disappearance of oral ulceration was evident following four weeks treatment and the patient is in regular follow up with maintenance therapy for last ten months. DOI: http://dx.doi.org/10.3329/medtoday.v25i2.17931 Medicine Today 2013 Vol.25(2): 99-102